Effects of High-Density Pulse Currents on the Solidification Structures of Cu-SiCp/AZ91D Composites - Xi Hao; Weixin Hao; Guihong Geng; Teng Ma; Chen Wang; Fuqiang Zhao; Hao Song; Yugui Li (Advances in Materials Science and Engineering)
In this study, Cu-SiCp/AZ91D composites were prepared with high-density pulse currents. The wettability between SiCp and matrix during solidification was improved by coating 0.095-μm thick copper film on the surface of SiCp. By comparing the composites prepared with/without pulse currents, the solidification structure and its formation mechanism of Cu-SiCp/AZ91D composites were analyzed under different conditions. The Cu-SiCp/AZ91D composites prepared without high-density pulse currents were mainly composed of α-Mg, β-Mg17Al12, and a small amount of Mg2Si phases, with coarse grains and uneven structures. Under the action of high-density pulse currents, the structures of Cu-SiCp/AZ91D composites were transformed into α-Mg and Mg2Si phases with refined grain, and the homogeneity of the structures was improved significantly.